2022
DOI: 10.1093/cercor/bhac241
|View full text |Cite
|
Sign up to set email alerts
|

A domain-general frontoparietal network interacts with domain-preferential intermediate pathways to support working memory task

Abstract: Working memory (WM) is essential for cognition, but the underlying neural mechanisms remain elusive. From a hierarchical processing perspective, this paper proposed and tested a hypothesis that a domain-general network at the top of the WM hierarchy can interact with distinct domain-preferential intermediate circuits to support WM. Employing a novel N-back task, we first identified the posterior superior temporal gyrus (pSTG), middle temporal area (MT), and postcentral gyrus (PoCG) as intermediate regions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In contrast, the left frontoparietal network mainly involves speech, semantic recognition, and cognition (Marek & Dosenbach, 2018 ; Vendetti & Bunge, 2014 ). Numerous neuroimaging studies have shown that abnormal right frontoparietal network activity might be closely related to impaired working memory and attention deficits (Becker et al., 2022 ; Chen et al., 2023 ; Letkiewicz et al., 2022 ; May & Kana, 2020 ; Tan et al., 2021 ; Yuk et al., 2020 ; Zhou et al., 2023 ). A previous neuroimaging meta‐analysis also dedicated that clinical patients with emotional regulation disorders exhibited reduced activity in the right frontoparietal network and compensatory activation of emotion‐related brain areas, such as the insula and temporal gyrus (Pico‐Perez et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the left frontoparietal network mainly involves speech, semantic recognition, and cognition (Marek & Dosenbach, 2018 ; Vendetti & Bunge, 2014 ). Numerous neuroimaging studies have shown that abnormal right frontoparietal network activity might be closely related to impaired working memory and attention deficits (Becker et al., 2022 ; Chen et al., 2023 ; Letkiewicz et al., 2022 ; May & Kana, 2020 ; Tan et al., 2021 ; Yuk et al., 2020 ; Zhou et al., 2023 ). A previous neuroimaging meta‐analysis also dedicated that clinical patients with emotional regulation disorders exhibited reduced activity in the right frontoparietal network and compensatory activation of emotion‐related brain areas, such as the insula and temporal gyrus (Pico‐Perez et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…shown that abnormal right frontoparietal network activity might be closely related to impaired working memory and attention deficits (Becker et al, 2022;Chen et al, 2023;Letkiewicz et al, 2022;May & Kana, 2020;Tan et al, 2021;Yuk et al, 2020;Zhou et al, 2023).…”
Section: Agementioning
confidence: 99%
“…Following our interpretation of the negative slow wave effect, it is possible that an indexical for event relations in the PPC (posterior parietal cortex) points to the event type represented in PLTC during working memory maintenance. However, evidence remains mixed on whether the event type representations in PLTC reflect the extraction of event types or the maintenance of event types in working memory, or both ( Lu et al, 2016 ; Zhou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Classically, sustained activity in lateral prefrontal cortex has been considered the primary neural mechanism underlying working memory [17]. Yet, just like other cognitive control abilities, this view is giving way to considering distributed CCNs as the basis for working memory [18]. As this shift was beginning, however, it was also revealed that working memory can be maintained in some situations without sustained activity, based on multi-unit lateral prefrontal cortical activity in non-human primates [19] and wholebrain electroencephalography (EEG) activity in humans [20,21].…”
Section: Connectivity-based Explanations For (Activity Silent) Workin...mentioning
confidence: 99%